Rainfall Indexation for Evaluating Rainfall Risk Profile of Indian Subcontinent - V., Bharath; G., Kotreshwar (Indian Journal of Finance, 2020)
This paper introduced a new set of rainfall indices which can be used as building blocks for designing rainfall derivatives contracts. Such a set was defined as deficit rainy days (DRD)/ excess rainy days (ERD) indices and computed for selected meteorological sub-divisions of India. The study aimed to explore the volatility and other statistical properties of DRD/ERD indices in order to assess the rainfall risk profile of the Indian subcontinent. The methodology proceeded in a step-wise form: Empirical values of DRDs/ERDs over 50 years for selected MSDs of India were derived, and then these index values were analyzed for determining the degree of variability, followed by the examination of the degree of intercorrelation amongst indices of selected meteorological sub-divisions. The paper provided insights on the behaviour of the volatility of the proposed indices and their potential application in designing rainfall derivatives contracts.